Congenital Melanocytic Naevi - A. C. Fledderus; C. J. A. vanEijsden; N. denHertog; M. S. vanKessel; A. Wolkerstorfer; M. M. Pleumeekers; S. G. M. A. Pasmans (JEADV Clinical Practice, 2025)
ABSTRACT Congenital melanocytic naevi (CMN) are birthmarks that can cover large areas of the body. CMN can significantly impact individuals' lives due to perceived stigma, the risk for melanoma development and neurological complications. To treat and prevent these complications, adequate research and guidelines are needed. In this review, we present a summary of the Dutch multidisciplinary guideline and the lessons learned from the implementation and information developed additionally in collaboration with the patient association. We also introduce the core outcomes of the OCOMEN project to standardize outcomes for both research and care of CMN. The next step is the development of the instruments internationally.